POSITIVE IMPACTS OF LOVE IN WILLIAM A. WELLMAN’S AND ROBERT CARSON’S MOVIE SCRIPT A STAR IS BORN - Cindy Yana Mentari; Devi Pratiwy (Universitas Islam Sumatera Utara, 2021)
This study aims to determine the positive impacts of love in the movie script A Star Is Born. This study is concerned with the types of love which imply the positive impacts. This study uses Fromm’s theory of love. The types of love analyzed in this study are brotherly love, erotic love, and self-love. Next, the positive impacts of love found in this study are for health, for personal ties, and for relationship. This study uses descriptive qualitative method to explain the types of love that imply positive impact, and positive impact of love from the quotations in the script. This film tells the story of an ordinary woman with great talent who accidentally meets a male celebrity who is addicted to alcohol. The man is attracted to the woman who has a dream to conquer Hollywood. He pushes her become a star. The results of this study show that love can have a positive impact for health that triggers Jack to be released from drugs and alcohol. Besides, the self-love in this movie is presented when Jack helps Ally to be more confident and love herself; consequently, she can be a successful songwriter and singer. Jack always loves her as she is. Ally always supports his health. Both of them strengthen and heal each other.